History of High Motion Sickness Susceptibility Predicts Vestibular Dysfunction Following Sport/Recreation-Related Concussion. Issue 4 (July 2019) - Sufrinko, Alicia M.; Kegel, Nathan E.; Mucha, Anne; Collins, Michael W.; Kontos, Anthony P.
Abstract : Objective: To compare vestibular dysfunction at 1 to 10 and 11 to 20 days following sport/recreation-related concussion (SRC) in athletes with and without history of motion sickness susceptibility. Secondary aims of this study were to investigate differences in neurocognitive performance and affective symptoms in these groups. Design: Cross-sectional. Setting: Concussion Specialty Clinic. Participants: One hundred twenty-four adolescents and adults (82 males, 42 females) aged 14 to 26 (16.36 ± 2.10) years, diagnosed with SRC in the past 10 (4.56 ± 2.54) days; 47 participants composed the sample for quartile analyses. Independent Variable: Motion sickness susceptibility questionnaire short form score. Main Outcome Measures: Computerized neurocognitive test scores, vestibular/oculomotor screening scores (VOMS), and symptom factor scores from a standardized concussion symptom inventory. Results: There was no association between history of motion sickness susceptibility and VOMS scores (above or below clinical cutoff) at 1 to 10 days after injury, although at 11 to 20 days after injury there was an association between high motion sickness susceptibility and symptoms above clinical cutoff on 5 of the 6 VOMS items ( P values 0.01-0.04). The high motion sickness group had more affective symptoms on the symptom inventory than the no motion sickness group ( P = 0.002) at 1 to 10 days after injury. Groups did not differ on computerized neurocognitive testing ( P = 0.11). Conclusion: Athletes with a preexisting history of motion sensitivity may exhibit more prolonged vestibular dysfunction following SRC, and may experience more affective symptoms early in recovery.